Improving the English Listening Skill by Taking Advantage of the Available Technologies - Rodríguez, Miriam; Lezama, Verónica; Otero, Franco; Castillo, María (CIEX JOURNAL, 2019)
This research explores the advantages of using Facebook as a virtual learning environment (VLE) in English language learning as well as the benefits of using different websites to develop the listening skill in the students of a public high school in the center of Mexico. The study was conducted following the procedure of quantitative research. First, by applying an experimental method and then by using a survey. In order to identify participants’ listening skill level, a pre-test and a post-test were applied. In addition, a survey was conducted to determine participants’ opinions. Findings demonstrate that Facebook is an excellent VLE that facilitates the process of teaching and learning English. They also identified that YouTube is an effective and interesting website to increase students’ listening skill, and moviemaker videos is an appropriate technological resource to monitor students’ progress.